Dermatofibrossarcoma Protuberans – a propósito de um caso clínico - Bôto, Carlos (2011)
Dermatofibrossarcoma protuberans (DFSP) is a rare malignant neoplasm, of slow growth, which rarely metastasizes and that has its source in the skin. This paper aims at presenting a clinical case of a 84 year old patient with DFSP, located in the thorax, with a 20 year evolution, who has had excision with Z-Plastic procedure. It also aims at presenting a literature review on the Dermatofibrossarcoma protuberans.